The Effects of Some Physical and Chemical Factors on Apparent Resistivity of Surface Soil in the University of Mosul, Mosul City, Northern Iraq - Al-Juraisy, Bashar A. (Iraqi Journal of Science, 2021)
Soil resistivity depends on many overlapping factors, which influence it in various ways. The aim of this study was to determine the effects of some physical and chemical factors on soil apparent resistivity. The results of field, laboratory, and statistical studies revealed a complex relationship between water content, pH, and salinity with soil apparent resistivity. The results showed that water content had a clear effect on apparent resistivity, as it increased significantly when water content value decreased to less than about 5%. The results also showed that increasing the salinity ratio at the expense of water content led to an increase in the apparent resistivity values. The apparent resistivity values also increased significantly when pH values ​​fell below about 7.7.The increase in air temperature caused an increase in water evaporation from the soil, which led to increasing the apparent resistivity. The rise in air temperature also caused an increase in the concentration of salts at the expense of water content; since salts are considered to be insulators, unless they are dissolved in water, they cause an increase in the value of apparent resistivity.